-3(x-4)+3x=12

Simple and best practice solution for -3(x-4)+3x=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x-4)+3x=12 equation:



-3(x-4)+3x=12
We move all terms to the left:
-3(x-4)+3x-(12)=0
We add all the numbers together, and all the variables
3x-3(x-4)-12=0
We multiply parentheses
3x-3x+12-12=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0

See similar equations:

| 15x-110=10x+75 | | u+110=-463 | | 8x+32=8x= | | x-147=14x+198 | | -3j=51 | | 13x-42=10x+30 | | 2/e=6 | | g+52=-17 | | -124-5x=11x+80 | | 4​x​+5=13 | | y+17=73 | | x-4/3+2x-3/9=10 | | 9.9x=45.9 | | 4(x+3)-6x=5x+8-(7x-4) | | 7​x​−2=−30 | | 45.9x=9.9 | | 65=f-10 | | 3x-5x+10=26 | | 45.9÷9.9=x | | 40x-20x=20 | | 268-y=138 | | 13=d−16 | | 62=-2(-9n-8)+10 | | 6x+30=4x+60 | | 209=69-x | | 238=-x+108 | | 0.006x=108000 | | y+32-y-44=0 | | 2.5k=2+0.3k+k | | 6y–1=5 | | 6x-2x=10+4x | | -70=5m-7(9m+10) |

Equations solver categories